PENGARUH KOMUNIKASI DALAM KELUARGA KRISTEN TERHADAP MORAL REMAJA GKPI DUMA SIRISIRISI KECAMATAN DOLOKSANGGUL TAHUN 2019 - Silaban, Angga Andika (IAKN Tarutung, 2020)
The research aimsto figure out how positive and significant a communication in Christian family towards adolescent moral of GKPI Duma Sirisirisi Kecamatan Doloksanggul 2019.The research hyphotesis : there is an positive effect and significant communication in Christian family towards adolescent moral of GKPI Duma Sirisirisi Kecamatan Doloksanggul 2019. This research is a study of population using descriptive method. Population is the whole adolescent of GKPI Duma Sirisirisi 2019 and the sum is 35 people. The instrument of this research is a questionnaire. The result of this analysis r hitung = 0,745 r tabel = 0,334and thitung= 6,415 t tabel = 2,034 shows that there is an effect amongst communication in Christian family towards adolescent moral of GKPI Duma Sirisirisi Kecamatan Doloksanggul 2019 and it obtains a significance of simple regression equations that is Ý = 15,523+ 0.848X. Hyphotesis testing obtains F hitung= 41,220F tabel = 1,97 then Ho is refused and Ha is accepted. This research concludes that the effect of communication in Christian family towards adolescent moral of GKPI Duma Sirisirisi Kecamatan Doloksanggul 2019 and it is 55,5% . Related to the result of this research, the writer gives such a suggestion for the observers particularly addressed to “parents” to carry on a communication in a family circle in order to create a good moral of adolescent ChristianKeywords : Communication in Christian family, adolescent moral